IMPLEMENTASI KEBIJAKAN PENGGUNAAN DANA BAGI HASIL CUKAI HASIL TEMBAKAU (DBHCHT) DI KABUPATEN PAMEKASAN - Fitriyah, Meliana (JURNAL AKUNTANSI DAN INVESTASI, 2017)
These research purposes are for knowing and understanding about how the implementation of utilizing of excising funds policies from tobacco products on Pamekasan in the year 2008 until 2013 and the effectiveness level of excising funds from tobacco products in Pamekasan. This research is including on quantitative description research category which describe about the implementation of utilizing of excising funds policies from tobacco products on Pamekasan in the year 2008 until 2013 and the effectiveness level of excising funds from tobacco products on Pamekasan in the year 2008 until 2013 by using effectiveness analysis approach which compare between budget and budget realization. Data analysis which used is in percentage form. The magnitude of the percentage is calculated by comparing budget realization and budget allocation. From data processing result known that the implementation of utilizing of excising funds policies from tobacco products on Pamekasan in the year 2008 until 2013 is appropriate with the rule of utilizing of excising funds from tobacco that exists, from finance ministry and the governor of East Java. Also found that the effectiveness level in the year 2008 is 80.76%. In the year 2009 is 74.19%. In the year 2010 is 43.86%. Whereas in the year 2011 decreased to 40.23%. So in the year 2012 rose to 86.08%, and in the year 2013 is 76.45%. From data analysis can be concluded that the excising funds from tobacco products in Pamekasan through economic administration of region secretary of Pamekasan as the secretary of excising funds from tobacco products in Pamekasan is not reached the effectiveness from 2008 until 2013.